Satisfaction of Patients after Urethral Reconstruction - Torabi Niaki, Seyed Ali; Aliakbari, Fereshteh; Sharifian, Rayka; Hosseini, Mohammad Ali; Hosseini, Jalil (Archives of Men’s Health, 2021)
Introduction: Urethroplasty is one of the most common and important reconstructive procedures in the field of urology. In order to improve patient’s condition, medical man needs to be acquainted with this technique. We aimed to evaluate quality of life and satisfaction of patients with Urethroplasty in the reconstructive urology department of Shohada-e-Tajrish Hospital, during 1995-2016. Materials and Methods: This study was a retrospective cohort. Sampling was done by census method. The patients’ demographic information, cause and duration of urethral stricture, type and frequency of procedures, daily fluid intake, urinary obstruction symptoms, the quality of marital relations, and the quality of life of patients before and after the surgery, were evaluated. Results: The mean age of the patients was 36.6 years. 46.4% of the patients had moderate and more than moderate marital satisfaction after surgery, while this preoperative satisfaction was 48.2% (P>0.05). Patients’ quality of work life and job satisfaction was significantly higher than before surgery (P=0.05). In 90.3% of the patients, urination status had no or little negative impact on their daily life after surgery. Also, 86.9% of the patients did not have weak urinary flow during follow-up. 88% of the patients were satisfied with the outcome of their surgery. Patients’ satisfaction with their physical health after surgery was 82.1%. Conclusion: In general, it is inferred that Urethroplasty is associated with a high success rate and patient satisfaction, and also improves their quality of life.